(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The aim of this paper is to provide an initial analysis of the Regulation (UE) on electronic health data, identifying the main innovative elements compared to the previous regulatory framework in this area. The objective is to assess its po-tential impact at the national level and to determine the necessary coordination measures to ensure the effective implementation of the outcomes envisaged by the European legislator. This cross-cutting analysis places particular emphasis on genetic and genomic data within the broader category of electronic health data, highlighting the different approach taken compared to the GDPR and the potential consequences this may entail.